The Confidence Building Measures (CBMs) between India and Pakistan - Younis Ahmad Sheikh (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
Confidence Building Measures (CBMs) play a crucial role in promoting stability and trust between India and Pakistan. This article, therefore, examines the different domains of CBMs, including political, military, economic, people-to-people, and nuclear, and highlights their significance in reducing tensions and fostering cooperation. Various examples of CBMs, such as hotlines between military authorities, cultural exchanges, economic cooperation, and religious pilgrimages, are explored to showcase their positive impact on communication and understanding. The paper also discusses the prospects and recommendations for CBMs, emphasizing sustained dialogue, economic cooperation, strengthened military CBMs, and exploring non-traditional security dimensions. By prioritizing CBMs, India and Pakistan can create a more stable and peaceful environment, paving the way for conflict resolution and long-term peace in the region. It is important to note that the study is completely based on secondary data; no primary research or data collection was conducted for this specific study.